The Utility of Cognitive Screening in Asian Patients With Heart Failure: A Systematic Review - Niu, Qi; Liu, WeiHua; Wang, FengLing; Tian, LiYa; Dong, YanHong (Frontiers in Psychiatry, 2022)
Background The prevalence of undiagnosed cognitive impairment in patients with heart failure is alarmingly high in Asia. There is still no consensus on cognitive screening tools to detect cognitive impairment in the Asian heart failure population. The clinical implications based on our systematic review may help to improve cognitive screening practice for patients with heart failure in Asia. Methods This review is registered in the PROSPERO (CRD42021264288). Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach, we searched PubMed, Embase, the Cumulative Index to Nursing and Allied Health Literature, Scopus, the Web of Science, PsycINFO, the Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, and Wanfang Data in English and Chinese literatures concerning heart failure and cognitive impairment. Results The search yielded 21 eligible studies. Only in five studies, cognitive brief tests, including the Montreal Cognitive Assessment (MoCA), the Mini-Mental State Examination (MMSE), and the Mini-Cog, were used as cognitive screening tools for Asian patients with heart failure. In the rest 16 studies, brief cognitive tests were used as screening tools for global cognition. Only one study validated screening tests against a gold standard formal neuropsychological assessment test battery. Among these studies, patients with heart failure tended to perform worse than patients without heart failure. The presence of cognitive impairment in patients with heart failure is associated with poorer self-care, quality of life, and hospital readmission. Conclusion Brief cognitive tests have been used in Asian patients with heart failure and these tests are frequently used as a measure of global cognitive function for cognitive screening. However, validating brief cognitive tests against a gold standard formal neuropsychological assessment in Asian patients with heart failure is lacking. Future studies need to address methodological issues to validate cognitive screening measures in a larger population of Asian patients with heart failure. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/